مراجعة حالات انتان الدم الفطري المكتسب في شعبة أمراض الوليد في مشفى الأسد الجامعي باللاذقية خلال الأعوام 2011-2014 - جوني, عدي (Latakia University Journal -Medical Sciences Series, 2018)
ترافقت التطورات الكبيرة ,التي حصلت في العقود الثلاثة الأخيرة في مجال العناية الوليدية والتي أدت الى ارتفاع معدل البقيا عند الخدج فائقي وشديدي نقص وزن الولادة , مع ارتفاع ملحوظ في معدلات حدوث انتان الدم الفطري المكتسب (من 2,6% الى 10% من الخدج شديدي وفائقي نقص وزن الولادة), الذي يرتبط حدوثه بمجموعة من العوامل التي تعتبر الخداجة الشديدة من أهمها, إضافة الى الاستخدام المديد للصادات الحيوية واسعة الطيف , التنبيب الرغامي المديد , القثاطر الوريدية المحيطية والمركزية , التغذية الوريدية الكاملة المديدة , إضافة الى البقاء الطويل في ظروف العناية المشددة . قررنا القيام بهذه الدراسة لتسليط الضوء على كل من عوامل الخطورة والسير السريري والانذار عند حديثي الولادة المقبولين في شعبة أمراض الوليد في مشفى الأسد الجامعي باللاذقية ,الذين تطور لديهم انتان دم فطري مكتسب, بغية الوصول الى استنتاجات وتوصيات يمكن ان تقود الى تجنب معدلات الحدوث المرتفعة لهذه الحالة المهددة للحياة . من هنا كان هدف الدراسة مركزا على القاء الضوء على الخصائص السريرية والمخبرية لانتان الدم الفطري المكتسب عند وضع التشخيص , ودراسة عوامل الخطورة المحتملة للإصابة عند حديثي الولادة في الشعبة المذكورة. . كان المعيار الذهبي لتشخيص حالات انتان الدم الفطري المكتسب في دراستنا هو النتائج الايجابية لزرع الدم بعزل الخمائر الفطرية عند جميع أطفال الدراسة . بدأت الهجمة السريرية لانتان الدم الفطري المكتسب عند ولدان مجموعة الدراسة مابين اليوم 7-26 للقبول في شعبة أمراض الوليد ( 9,4+13 يوم) . سجل عدم الاستقرار الحروري ,مع ميل نحو الانخفاض, عند 40% من مجموعة أطفال الدراسة وعند 10% فقط من أطفال مجموعة المراقبة . سجلت حالات تمدد البطن عند 45% من أطفال مجموعة الدراسة وعند 15% فقط من أطفال مجموعة المراقبة, سجلت حالات الخمول عند 47,5%من أطفال مجموعة الدراسة وعند 10% فقط من أطفال مجموعة المراقبة , وجدنا الثمالة المعدية عند 40% من أطفال مجموعة الدراسة وعند 15% من أطفال مجموعة المراقبة. .لم يسجل التهاب السحايا الفطري عند أي من أطفال الدراسة. بلغ مجموع الوفيات في مجموعة الدراسة 11 حالة وفي مجموعة المراقبة 6 حالات . سجل التعداد الانتاني للكريات البيض والمعتدلات عند( 42,5% ,45% على الترتيب )من مجموعة انتان الدم الفطري المكتسب, بالتزامن مع وضع التشخيص . كما سجل نقص الصفيحات الدموية عند معظم أطفال عينة الدراسة ( 92,5%) والتي أمكن الاعتماد عليها في التوجه الى إمكانية تطور حالة انتان الدم الفطري المكتسب عند حديث ولادة يخضع لظروف العناية المشددة وتتوفر لديه عوامل الخطورة لتطور الانتان المذكور. كانت القثاطر الوريدية المحيطية طويلة الأمد والتنبيب الرغامي والتداخلات الطبية والجراحية والصادات الحيوية واسعة الطيف أهم عوامل الخطورة لتطور الحالة , من هنا نستنتج ان اعتماد بروتوكولات خاصة بالوقاية من انتان الدم الفطري المكتسب واتباع إجراءات التعقيم الدوري لشعب العناية بحديثي الولادة يمكن أن تقلل من احتمال تطور الحالة .كما أن المعالجة النوعية المضادة للفطور يجب أن تبدأ مباشرة بعد أخذ عينات الزرع التي تتم على أساس الشك السريري والمخبري (عدم الاستقرار الحروري ,نقص الصفيحات الدموية ..) مما يساهم الى حد كبير في الشفاء من انتان الدم الفطري المكتسب دون أية اختلاطات مهمة . The major developments in the last three decades which related to the neonatal care, led to a high rate of survival in very and extremely low birth weight infants. These developments also led to a significant increase in the incidence of AFS* (from 2.6% to 10% ). Which is associated with a combination of factors that are considered the most severe prematurity, in addition to the long-term use of broad-spectrum antibiotics, long tracheal intubation, peripheral and central venous catheters, long-term total parenteral nutrition, and long survival in intensive care conditions. We decided to carry out this study to highlight the risk factors, clinical presentations and prognosis for AFS in the neonatal care department at Al-Assad University Hospital in Lattakia, and thus reaching conclusions and recommendations that avoid high incidence rates of this life-threatening condition. The aim of the study was to shed light on the clinical and laboratory characteristics of the AFS when developing the diagnosis and to study its potential risk factors for its occurrence of neonates in the department of neonatal care. The gold standard for diagnosing AFS in our study was the positive results of blood culture by isolating fungal yeasts from all neonates of the study sample. The clinical onset of the AFS in study group was started between 7-26 days(9,4 + 13 days) of admission to the neonatal care division . Thermal instability with a downward tendency was recorded in 40% Of neonates study group and in 10% of the neonates control group . Abdominal expansion was recorded in 45% of the study group and only in 15% of the control group . lethargy was recorded In 47,5% of the study group and in 10% of control group , we found gastric residues in 40% of neonates of the study group and in 15% of the control grpup. The total number of deaths was 11 cases in the study group and 6 cases in the control group . at the time of diagnosis, the infectious leukocyte and neutrophyls count were recorded at( 42.5% , 45% respectively) , The incidence of thrombocytopenia was recorded in the most of the study group (92.5%), which can be relied upon to develop the possibility of the development of the AFS in a newborn born under the conditions of intensive care and have risk factors for the development of infection . Long term peripheral venous catheters, endotracheal intubation, medical and surgical interventions, and broad-spectrum antibiotics were the most important risk factors for the development of AFS. Thus, we conclude that the adoption of protocols for the prevention of this situation and periodic sterilization procedures for the neonatal care unite can reduce the likelihood of developing AFS. The specific anti-fungal treatment should begin immediately after taking samples for blood culture , on the basis of clinical and laboratory suspicion (eg, thermal instability, thrombocytopenia), which greatly contributes to the healing of the condition without any complications.